Does ocean acidification increase the susceptibility of Mytilus edulis mussels to pollution? - Logan, Iain (University of Exeter, 2016)
Ocean acidification (OA), caused by the absorption of vast quantities of CO2 at a high rate by the oceans, is considered to be capable of causing large-scale ecosystem changes through its impacts on calcification, acid-base balance and energetics in a wide range of marine organisms. An area which has received little attention with regard to OA is the impact of multiple stressors, specifically pollutants and how reducing seawater pH levels will affect their impacts on marine species. The now banned anti-fouling agent tributyltin (TBT) is predicted by speciation chemistry to reduce in bioavailability as pH levels reduce. Here I investigate whether this reduced speciation leads to reduced toxicity under OA in the mussel Mytilus edulis. Mussels exposed to TBT under experimental OA conditions (seawater pH 7.7) were found to experience 45% greater DNA damage than those exposed under ambient pH conditions. Slight changes in acid-base physiology were also observed. To investigate potential biological mechanisms underpinning the observed increase in TBT toxicity under OA conditions, mussel gaping behaviour and respiratory physiology during tidal cycles were then investigated under OA relevant seawater pH levels. It was found that previously starved mussels gape more at lower pH levels and that mussel haemolymph pCO2 differs significantly (p=0.009) between different seawater pH treatments during a simulated tidal cycle while the level of oxygen in the haemolymph does not, providing evidence that CO2 may be the driver behind mussel respiration rather than O2. This work demonstrates that M. edulis is more vulnerable to pollutants at OA relevant pH levels due to increased mussel gaping, driven by the need to reduce haemolymph pCO2 levels, which results in the mussel filtering more water and taking on more TBT as a consequence. These behavioural and physiological responses to OA are likely to increase susceptibility to a whole range of pollutants, not just TBT, by increasing potential uptake.